2005
DOI: 10.1002/ejic.200500711
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Triple‐Stranded Dinuclear Helicates with Dicatecholimine Ligands: The Influence of Steric Hindrance at the Spacer

Abstract: A series of new imine‐bridged dicatechol ligands 3a–f‐H4 with sterically demanding groups at the spacers are used for the formation of titanium(IV) complexes M4[(3)3Ti2]. All three ligands 3a–c‐H4 form triple‐stranded dinuclear helicates. When the bulky ligands 3a‐H4 or 3c‐H4 are used with potassium as the countercation, oligomeric or polymeric side products are also observed. The imine‐bridged ligand 3e‐H4 quantitatively forms helicates M4[(3e)3Ti2] and not a M4L6 tetrahedron as observed with Raymond’s analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…1 and 2A) (33,34). Assembly 1 exhibits 12 intramolecular amide hydrogen bonds which, in analogy to structurally important peptide bonds found in polypeptides, preferentially stabilize the desired tetrahedral supramolecular structure over other conformers (35). Compound 1 and related hosts have been shown to catalyze several important chemical reactions with sizable rate accelerations (up to 10 6 ) and unusual selectivity reminiscent of enzyme catalysis (34,(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…1 and 2A) (33,34). Assembly 1 exhibits 12 intramolecular amide hydrogen bonds which, in analogy to structurally important peptide bonds found in polypeptides, preferentially stabilize the desired tetrahedral supramolecular structure over other conformers (35). Compound 1 and related hosts have been shown to catalyze several important chemical reactions with sizable rate accelerations (up to 10 6 ) and unusual selectivity reminiscent of enzyme catalysis (34,(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…For example, variation of the stereo-controlling units between dicatecholate groups can result in the formation of triple-stranded mesocates in preference to helicates. [7,8] In these systems, however, it is likely that hostguest solvate interactions are the primary factor in favouring helicate or mesocate structures. [14] It has also been found that increasing the steric bulk from H to Et at the ortho positions of the phenyl spacers in double-stranded dicopper iminopyridine complexes promotes a helical twist at the methylene position, and so results in a change from a mixture of meso and rac diastereomers to purely rac-helicates.…”
Section: Helicate Formationmentioning
confidence: 98%
“…Racemic mixtures of metallohelicates can be separated by fractional crystallisation or by chromatographic techniques, [3] but a second chiral entity, such as a chiral anion or other templating agents, [4] and/or chiral ligands, [5][6][7] are necessary to direct the selective synthesis of single enantiomer helicates. The preferential, and diastereoselective, synthesis of mesocates instead of helicates appears controlled by a variety of factors, such as the modification (chiral or not) of the spacer unit between the two donor compartments, [8][9][10] the variation of the metal, [11][12][13] and the incorporation of a guest molecule. [14] [a] School of Chemistry, University We identified previously the donor-extended dipyrromethane H 2 L 1 (Scheme 1) as a ligand that is suitable for use in the synthesis of neutral, dinuclear metallohelicates due to the rigidity of the iminopyrrole chelates, the preference of iminopyrrole to pyrrole-pyrrole chelation in the potassium salt of the meso-CPh 2 analogue, {K 2 [tBuN=CH-(C 4 H 2 N) 2 CPh] 2 }, [15] and the presence of the sp 3 of opposing ligand strands; this interaction is observed both in the solid state and in solution at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To produce a “true” helicate assembly, the ligand must adopt an S‐type arrangement where each of the metal binding domains coordinates a different metal ion but the ligand twists in the centre, generating the homochiral (ΔΔ or ΛΛ) helicate. If the ligand coordinates two different metal ions but the ligand strand does not twist (referred to as a C‐type arrangement) then this “side‐by‐side” complex is referred to as the achiral (ΔΛ or ΛΔ) meso helicate (or mesocate) …”
Section: Figurementioning
confidence: 99%